(INDUKSI REGENERASI IN VITRO PADA SPESIES TANAMAN PENGHASIL GUBAL GAHARU, Aquilaria filaria) - Baiq Erna Listiana (Department of Agronomy Faculty of Agriculture University of Mataram and Indonesian Society of Agronomy Branch NTB, 2017)
ABSTRACT Aquilaria filaria is one of the species producing precious fragrant oleoresin agarwood which is endemic in Eastern of Indonesia. In 2004 CITES (Convention on International Trade in Endangered Species of Wild Fauna and Flora) incorporated A. filaria as vulnerable species due to the declining population of this plant in their habitat of origin. Propagation of this plant species is essential for continuation of agarwood supply and preservation of genetic resources. Biotechnological approach by plant in vitro culture is advanced preservation technique for genetic resources. Plant in vitro culture is not only strategy to propagate plant material in prolific rates for in situ and ex situ germplasm preservation in range of environmental condition, but also answer the problem in seed recalcitrant and less viability as well as studying genetic and physiology of the plant. Up to date there is no available information of in vitro regeneration in Aquilaria filaria plant. This research aims to study de novo regeneration of shoot and root in plant tissue culture of Aquilaria filaria for the basis of in vitro preservation of this vulnerable plant species. The research includes callus induction, shoot regeneration from plant callus and root regeneration from shoot explants. In vitro cultivation conducted in Murashige and Skoog (MS) medium containing phytohormone auxin: indole-3-butyric acid (IBA), α-naphthalene acetic acid (NAA) and 2,4-dichlorophenoxyacetic acid (2,4-D) and cytokinin: 6-benzylaminopurine (BAP) and kinetin. The result reveals that leaf is competent material for callus induction. High proliferating callus is induced in medium containing combination of IBA (2 mg/l) or NAA (0.2 – 1 mg/l) with cytokinin BAP (0.5 – 1 mg/l). A. filaria plant callus regenerate shoots primordia by an addition of single BAP (0.5 mg/l) or combination with IBA or NAA (0.2 mg/l)) into the culture medium. Moreover, rooting of shoot cultures achieve in medium with additional of sole phytohormone IBA (1 – 2 mg/l) or NAA (0.2 – 2 mg/l). The result of this study provides basis for in vitro propagation of A. filaria and further assessment related agarwood producing species. ABSTRAK Aquilaria filaria adalah salah satu spesies penghasil gaharu, gubal wangi bergengsi tinggi, yang endemik di Indonesia bagian timur. Pada tahun 2004 CITES (Convention on International Trade in Endangered Species of Wild Fauna and Flora) memasukkan A. filaria sebagai spesies yang langka karena penurunan populasi dari tanaman ini pada habitat aslinya. Oleh karena itu, perbanyakan dari spesies tanaman ini sangat penting untuk keberlanjutan suplai gaharu dan pelestarian sumber genetik. Pendekatan biotechnologi melalui kultur in vitro tanaman adalah teknik terdepan untuk pelestarian sumber genetik. Budidaya tanaman in vitro tidak hanya strategi untuk memperbanyak tanaman secara masal untuk pelestarian sumber genetik pada kondisi linggungan yang luas, tetapi juga menjawab permasalahan benih rekalsitran dan viabilitas rendah, selain juga untuk mempelajari genetik dan fisiologi dari tanaman tersebut. Hingga saat ini belum ada informasi yang tersedia mengenai regenerasi in vitro pada tanaman Aquilaria filaria. Penelitian ini bertujuan untuk mempelajari de novo (permulaan) regenerasi pucuk dan akar pada kultur jaringan tanaman Aquilaria filaria sebagai basis pelestarian in vitro dari spesies tanaman ini. Penelitian ini termasuk induksi kalus tanaman, regenerasi pucuk dari kalus tanaman dan regenerasi akar dari eksplan pucuk. Kultur in vitro dilakukan menggunakan medium Murashige and Skoog (MS) yang mengandung phytohormone auxin: indole-3-butyric acid (IBA), α-naphthalene acetic acid (NAA) and 2,4-dichlorophenoxyacetic acid (2,4-D) dan cytokinin: 6-benzylaminopurine (BAP) and kinetin. Hasil penelitian ini menunjukkan bahwa daun adalah material yang kompeten untuk induksi kalus. Proliferasi kalus yang tinggi terinduksi pada medium yang mengandung kombinasi IBA (2 mg/l) atau NAA (0.2 – 1 mg/l) dengan cytokinin BAP (0.5 – 1 mg/l). Kalus tanaman A. filaria beregenerasi menjadi pucuk primordial dengan penambahan BAP (0.5 mg/l) atau kombinasi IBA atau NAA (0.2 mg/l)) kedalam medium kultur. Selanjutnya pengakaran dari kultur pucuk didapatkan pada medium dengan hanya penambahan IBA (1 – 2 mg/l) atau NAA (0.2 – 2 mg/l). Hasil penelitian ini memberikan basis bagi propagasi in vitro A. filaria dan penelitian lanjutan bagi spesies tanaman penghasil gaharu.